PELATIHAN KETRAMPILAN PENCEGAHAN PENYALAHGUNAAN NARKOBA BAGI PRA REMAJA DAN REMAJA DI KOTA JOGJAKARTA - , Prabandari, Yayi Suryo et ([Yogyakarta] : Lembaga Penelitian UGM, 2003)
Drugs misuse has a great impact, not just limited to the user instead also could endanger others surroounding. The existence data showed that drugs user is not just limited to adults, but has widely spread to teenager. Most of them started from willingness to try, and the result of environment influence. Based on the previous research result, it is known that the most approciate effort to apply drugs misuse prevention skill in pre teenager and teenager was giving social skills training to them. Beside that, this effort also accompanied by giving training to parents so that they are able to give the right information to their children and also participated in the effort of drug misuse prevention skill. This research was aimed to find out the effectiveness of training skill of drugs misuse prevention in pre teenagers and teenagers as well as their parents.